Connecting Women with Unions: What Are the Issues? - Forrest, Anne (Relations industrielles / Industrial Relations, 2001)
SummaryThis paper investigates the role of “women’s issues” in the decision to join unions by examining a successful organizing drive in a predominantly female workplace. The main focus of the discussion is the identification of women’s issues where they were not immediately apparent to workers and union representatives. The theoretical question raised by this case study is the extent to which women workers’ relationship to unions is similar to or different from men workers’. Contemporary industrial relations discourse tends to emphasize the similarities between women and men, without taking into account well-documented differences in women’s paid and unpaid work and union experiences. From a feminist perspective, the conclusion that gender is unimportant in organizing campaigns often rests on an inadequate analysis of what constitutes women’s workplace/union issues.